When Oriole traveled westward - Marlowe, Amy Bell (Salt Lake City, UT : Project Gutenberg, 2025)
"When Oriole Traveled Westward" by Amy Bell Marlowe is a children's adventure novel written in the early 20th century. It follows spirited Oriole Putnam from a New England harbor toward the wide-open West as she bonds with a rancher$1 (Bs twins, meets a troubled boy from Montana, and pursues the mystery of her missing parents. Expect family bonds, courage in sudden danger, and a journey that promises ranch-country adventures. The opening of the novel finds Oriole skating across a frozen harbor with her twin charges when a racing iceboat forces them into the water; a stranger, Teddy Ford, dives in and saves them. Grateful yet wary, Teddy reveals he once worked for the twins$1 (Bfather, rancher Harvey Langdon, who accused him of stealing family silver; at Oriole$1 (Bs urging he resolves to return West and clear his name. Langdon retrieves the twins, appreciates the rescue, invites Oriole to visit the ranch, and prepares to head home with the children and their recovering nurse. Meanwhile, school-day tensions surface in a prank gone wrong when a neighbor boy$1 (Bs ram smashes a sun-parlor window. Finally, sobering news arrives from a rescued sailor: Oriole$1 (Bs father likely perished during the evacuation of the Helvetia, while her mother may have been picked up by a tramp ship, leaving hope$1 (Band questions$1 (Babout her whereabouts. (This is an automatically generated summary.)s
Release date is 2025-06-04
Aaron Adrignola, Mary Meehan and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Western stories; Schools -- Juvenile fiction; Twins -- Juvenile fiction; Rescues -- Juvenile fiction; Girls -- Societies and clubs -- Juvenile fiction; Ranch life -- Juvenile fiction; Cowgirls -- Juvenile fiction; Outlaws -- Juvenile fiction